Prospective Foodborne Disease Epidemiology Studies in Ethiopia: Cross-Sectional Healthcare Worker Study - Kowalcyk, Barbara; Alonso, Silvia; Gazu, Lina; LaPolt, Devin; Azmeraye, Binyam; Teshale, Amete; Ngwili, Nicholas; Angaw, Dessie; Ayana, Galana; Beczkiewicz, Aaron; Garsow, Ariel; Barkley, James; et al. (2025)
This is a working package under a bigger project named "Estimating the public health burden of Salmonella, Shiga toxin-producing E. coli, and Campylobacter in Ethiopia" (TARTARE) funded by the Bill and Melinda Gates Foundation and the United Kingdom Department for International Development.